THE ROLE OF TECHNOLOGY IN THE ECONOMY IN THE DIGITAL ERA - Taufiqurokhman, Muhammad Dzakwan (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this research is to analyze and explain the optimization of the role of collaboration and the role of technology in the economy in the digital era. The data of this study is MSMEs in SUKABUMI City with a population of 31,926 people and is used as a sample in this study as many as 100 business actors taken using a simple size web.raosoft.com with an error rate of 10%. The research method uses a quantitative research method, with a data collection method, namely the distribution of questionnaires through google-form of statements to respondents and interviews. Simple linear regression analysis is used as the analysis method in this study. The results of the study explained that there was a positive influence of technology on the economy in Sukabumi City with a large influence of 61.2% and 38.8% influenced by other variables.